PROMISING WATERMELON VARIETY ‘METEOR’ - S. V. Malueva; E. A. Varivoda; I. N. Bocherova (Овощи России, 2018)
Watermelon is one of the most common crops of medium melons. Biological peculiarities of cultivation of watermelon allow using global warming as a factor expanding the area for cultivation. Breeding work is carried out to develop new varieties and hybrids of watermelon suitable for cultivation in more Northern areas of the Russian Federation with a shorter vegetation period In Bykovskaya Melons and Gourds Experimental Breeding Station. To accomplish this goal the creation of new varieties of watermelon, early maturity with excellent taste, friendly fruit ripening, drought-resistant, suitable for intensive cultivation technology is carried out. Currently, the new early maturing variety of watermelon ‘Meteor’ with a growing period for 65-70 days and dry matter content to 12.0% has been transferred to the State Variety Trial. According to research results, comparative characteristics between new promising variety ‘Meteor’ and control variety ‘Zenith’ were given. The ‘Meteor exceeded the standard variety in yield ability by 19.0 сwt/ha. According to pathogen tests for complex resistance the ‘Meteor’ exceeded the control by 6.4 % for Fusarium, and scored at 0.8 against Anthracnose attack.